Motiv posta i molitve u hrvatskoglagoljskim tekstovima 15. i 16. stoljeća - Dürrigl, Marija Ana (2019)
Motiv posta i molitve često se zatječe u djelima raznih sadržajnih, oblikovnih i vrsnih pripadnosti tijekom mnogih stoljeća, pa je moguće govoriti o motivu dugoga trajanja. U trima se glagoljskim kodeksima iz 15. i 16. stoljeća (u tzv. Oxfordskom, Berčićevu i Grškovićevu zborniku) nabrajaju osobe iz Biblije i svetci koji su postili i tako postigli spas i milost. U tim je spomenicima popis likova u velikoj mjeri podudaran. Po tonu i stilu zaključuje se kako su tekstovi bili namijenjeni širem krugu primatelja, a ne (samo) užoj redovničkoj ili duhovničkoj zajednici. Tekstovi su analizirani s književnoteorijskoga polazišta, s naglaskom na njihovoj strukturu, a identificirane su dvije važne karakteristike hrvatskoglagoljske proze. To su polifunkcionalnost, jer djela često ujedinjuju praktične (npr. pastoralne, moralne i poučne) funkcije s estetskom, te otvorenost forme, jer se teme, motivi i slike pojavljuju u uvijek novim kombinacijama i kontekstima (specifična intertekstualnost). U analiziranim se tekstovima prepoznaju figure i tropi tipični za hrvatsku srednjovjekovnu prozu (npr. antiteza, paregmenon, nabrajanja, dijade, trijade, asonancije, sintaktički i leksički paralelizam).
The Croatian Glagolitic medieval literature consisted mostly of religious texts (e.g. hagiographies, visions, debates/contrasts, Miracles of the Blessed Virgin, dialogue poems, miracle and morality plays). Some of them contain the motif of fasting and prayer as well as the benefits of self-renunciation, allowing men to become purer and better in their relationships towards both themselves (through fasting and self-renunciation) and other people (through good deeds and almsgiving), and to achieve a closer relationship with God (through prayer). The motif of fasting and prayer is frequently found in texts of various themes, forms, and genres over the centuries. It was present in European Christian literature from its beginnings to the early modern period, making it a long-standing motif. During the Middle Ages in Europe, that motif was most notably found in moral-didactic and pastoral texts, but also in narrative prose texts. Three Croatian Glagolitic manuscript codices were chosen for this research: Oxford Miscellany (15th c.), Berčić Miscellany (15th c.) and Gršković Miscellany (16th c.), as collections of texts exhibiting motifs of fasting, prayer and works of mercy. The recombination of the motif in different contexts (as a sermon in a debate, as a motif in a legend and as a starting point of a moral-didactic text) reflects the memory-based nature of medieval culture – that which is adopted as one’s own, can be recombined rather freely. The three Glagolitic codices list Biblical figures and saints who found salvation from evil through fasting and prayer (e.g. Isaac, Lot, Susanna, Daniel, three young men in the fiery furnace, Saint Thecla, and Saint Margaret) and those in various ways blessed by God (e.g. Moses, Elijah, Joachim and Anne, the apostle Paul, Saint Nicholas, Saint Benedict). The list of characters is consistent to a large extent in all three manuscripts.
Bilješke uz tekst.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Hrvatskoglagoljska književnost -- Književni motivi -- Kršćanski motivi; Srednji vijek -- Rani novi vijek